2021
DOI: 10.3389/fonc.2021.768222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Targeted Microbubble Destruction Alleviates Immunosuppression Induced by CD71+ Erythroid Progenitor Cells and Promotes PDL-1 Blockade Immunotherapy in the Lewis Lung Cancer Model

Abstract: The CD71+ erythroid progenitor cells (CECs) exhibit distinctive immunosuppressive properties and regulate antitumor immunity to enable tumor growth. We presented a novel and non-invasive approach to improving immunity by targeting the splenic CECs via sonoporation generated by ultrasound-targeted microbubble destruction (UTMD). The systematic immunity enhanced by the reduction of PDL-1-expressing CECs also benefits the PDL-1 blockade therapy. In the Lewis lung cancer (LLC) model, the study group was treated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…2c ). Similarly, one recent study elucidated that UTMD decreased the frequency of CD71 + erythroid progenitor cells, which suppress the immune response [ 74 ] (Fig. 2d ).…”
Section: Effects Of Utmd On Tumour-infiltrating Myeloid Cellssupporting
confidence: 54%
See 2 more Smart Citations
“…2c ). Similarly, one recent study elucidated that UTMD decreased the frequency of CD71 + erythroid progenitor cells, which suppress the immune response [ 74 ] (Fig. 2d ).…”
Section: Effects Of Utmd On Tumour-infiltrating Myeloid Cellssupporting
confidence: 54%
“…UTMD with pIFN-β and anti-PD-1 also slowed tumour growth by 4-fold and even showed complete tumour regression by enhancing T-cell recruitment in a mouse model of breast cancer [ 51 ]. For the Lewis lung cancer (LLC) model, UTMD and anti-PD-L1 combination therapy induced an increase in IFN-γ production, causing an increase in CD8 + T-cell frequency to inhibit LLC progression [ 74 ]. Moreover, researchers constructed TLR agonist (R837)-loaded pH-responsive liposomes (PEOz-Lip@R837) to treat pancreatic cancer.…”
Section: Enhanced Antitumor Efficacy In Different Cancer Species With...mentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Ultrasound targeted microbubble destruction combined with PD-L1 blockade can promote the activation and differentiation of CD8+ T cells, increase IFN-γ secretion, reverse an immunosuppressive microenvironment, enhance acquired immunity, and inhibit tumor growth. 42 Kim et al 43 developed a PD-L1 targeted immune microbubble complex that can not only reduce the immune-related toxicity induced by antibodies but also improve the therapeutic efficacy when combined with focused ultrasound. In addition, Li et al 44 found that the ultrasound stimulation of microbubble cavitation could promote tumor blood perfusion, enhance CD8+ T cell infiltration, and PD-L1 antibody delivery, thereby increasing the number and activity of CD8+ T cells and thus generating strong antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [49] Spleens of LLC tumour-bearing mice were in the first study divided into two groups: (1) US+CA and (2) untreated. The CAs were Sonazoid MBs.…”
Section: Author Treatment Protocol Us Parameters Main Findingsmentioning
confidence: 99%